MetOcean data to linked data - Danyaro, K.U. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper describes the Linked Data initiative in meteorological environment. MetOcean data are meteorological and oceanographic datasets that provide information to meteorological industries, petroleum industries as well as research institutes. The MetOcean has a myriad of data and scattered along the globe which lack Linked Data or Semantic Web capabilities. Linked Data is a concept of publishing interoperable data globally. As a way of integrating MetOcean data, this work used D2R server, a server that manages data sources and translates it to Web data. Therefore, the paper elucidates the process of developing Linked Data in Meteorological sector. Also, the results were queried using SPARQL endpoint as a graph. This approach was analyzed using F-measure which reveals the system is sufficient for querying and accessing the data as a graph. Â© 2014 IEEE.